Editorial - Albuquerque, Carlos (2021)
THE INVISIBLE BEINGS THAT THREATEN HUMANITY: RELEVANCE OF VACCINATION  When in the late 18th century (1798), the British naturalist and rural physician Edward Jenner Monticello (1749-1823), now widely known as the “father of immunology”, discovered one of the most famous medicines - the first vaccine against smallpox - The evolution of medicine and, consequently, of the world took a colossal step. In this way, the first drug that was not intended to cure, but to prevent, was discovered, trying to prevent people from becoming infected by that disease that would certainly lead to death. Here is the discovery of preventive drug therapy, which would become one of the most important historical landmarks of medicine in favor of humanity, a feat witnessed by Thomas Jefferson (third president of the United States of America) in his letter, on the 14th of May 1806, to Edward Jenner Monticello: “I avail myself of this occasion of rendering you a portion of the tribute of gratitude due to you from the whole human family. Medicine has never before produced any single improvement of such utility. (...) You have erased from the calendar of human afflictions one of its greatest.”1